2014
DOI: 10.1007/s00296-014-2995-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of opioid receptor μ1 gene A118G polymorphism and its association with pain intensity in patients with fibromyalgia

Abstract: Fibromyalgia may present with widespread pain and tenderness, fatigue, anxiety, and depression and is associated with a low pain threshold. The etiology of fibromyalgia is yet to be ascertained, although both genetic and environmental factors may play a role in the susceptibility of patients to fibromyalgia. Various genetic variations have been investigated to explain fibromyalgia susceptibility and differences in pain sensitivity, pain threshold, and tolerance. The A118G rs1799971 polymorphism in the opioid r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 23 publications
2
8
0
2
Order By: Relevance
“…The activity of these structures is modulated by μ-opioid receptor availability, which is reduced in fibromyalgia [ 23 ]. In agreement with a study in Turkey [ 10 ], our findings suggest that the rs1799971 SNP confers fibromyalgia susceptibility, as most of the present patients’ sample were GG genotype (55.8%) and most of the controls were AA/AG (57.7%).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The activity of these structures is modulated by μ-opioid receptor availability, which is reduced in fibromyalgia [ 23 ]. In agreement with a study in Turkey [ 10 ], our findings suggest that the rs1799971 SNP confers fibromyalgia susceptibility, as most of the present patients’ sample were GG genotype (55.8%) and most of the controls were AA/AG (57.7%).…”
Section: Discussionsupporting
confidence: 93%
“…Guanosine triphosphate cyclohydrolase 1 (GCH1) and opioid receptor μ1 (OPRM1) are candidate neurotransmitter-related genes that may confer fibromyalgia susceptibility [ 9 , 10 ]. GCH1 gene participates in the synthesis of dopamine and serotonin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthy individuals possessing at least one copy of the variant G allele have been reported to exhibit lower pressure pain sensitivity (Fillingim et al, 2005) and women heterozygous or homozygous for the variant G allele reported experiencing less pain after sexual assault (Ballina et al, 2013). The allelic frequency of the A118G SNP was lower in fibromyalgia patients, suggesting a possible protective role for this chronic pain condition (Solak et al, 2014). However, a meta-analysis of eight clinical studies failed to find a consistent association between the A118G SNP and pain response (Walter and Lotsch, 2009).…”
Section: 1 Discussionmentioning
confidence: 99%
“…Se ha reportado, además, que en células CHO (del inglés, chinese hamster ovary) transfectadas con MOR-D, los niveles de expresión de ARNm y proteínas de este receptor son menores que en aquellas transfectadas con el receptor silvestre MOR-N (Zhang et al, 2005 (Sia et al, 2008;Tan et al, 2009), y un aumento de los requerimientos de opioides en pacientes con dolor post-operatorio (Klepstad et al, 2004;Chou et al, 2006a;Chou et al, 2006b;Sia et al, 2008;Tan et al, 2009). Sin embargo, otros estudios no pudieron encontrar estas asociaciones (Pettersson et al, 2012;De Gregori et al, 2013;Solak et al, 2014;Xu et al, 2014) o inclusive encontraron asociaciones opuestas (Janicki et al, 2006;Song et al, 2013). Dados los múltiples componentes genéticos de las poblaciones mundiales actuales, se ha propuesto que las discrepancias entre estos estudios se deben a la contribución de un proceso de estratificación poblacional en la constitución de los fenotipos observados (Levran et al, 2011).…”
Section: El Receptor Opioide µunclassified